Electromagnetic response of a highly granular hadronic calorimeter - Adloff, Catherine; Schultz-Coulon, Hans-Christian; Shen, Wei; Stamen, Rainer (Journal of Instrumentation, 2011)
The CALICE collaboration is studying the design of high performance electromagnetic and hadronic calorimeters for future International Linear Collider detectors. For the hadronic calorimeter, one option is a highly granular sampling calorimeter with steel as absorber and scintillator layers as active material. High granularity is obtained by segmenting the scintillator into small tiles individually read out via silicon photo-multipliers (SiPM). A prototype has been built, consisting of thirty-eight sensitive layers, segmented into about eight thousand channels. In 2007 the prototype was exposed to positrons and hadrons using the CERN SPS beam, covering a wide range of beam energies and angles of incidence. The challenge of cell equalization and calibration of such a large number of channels is best validated using electromagnetic processes. The response of the prototype steel-scintillator calorimeter, including linearity and uniformity, to electrons is investigated and described.
*The CALICE collaboration: C. Adloff, H.-Ch. Schultz-Coulon, W. Shen, R. Stamen [und 169 weitere Personen]
Gesehen am 28.02.2022